Pooled Analysis of Real-World Evidence Supports Anti-CGRP mAbs and OnabotulinumtoxinA Combined Trial in Chronic Migraine - Damiana Scuteri; Paolo Tonin; Pierluigi Nicotera; Marilù Vulnera; Giuseppina Cristina Altieri; Assunta Tarsitano; Giacinto Bagetta; Maria Tiziana Corasaniti (Toxins, 2022)
OnabotulinumtoxinA, targeting the CGRP machinery, has been approved for the last two decades for chronic migraine prevention. The recently approved monoclonal antibodies (mAbs) directed towards the calcitonin gene-related peptide (CGRP) pathway open a new age for chronic migraine control. However, some 40% patients suffering from chronic migraine is still resistant to treatment. The aim of this work is to answer the following PICOS (participants intervention comparator outcome study design) question: Is there evidence of efficacy and safety of the combined administration of anti-CGRP mAbs and onabotulinumtoxinA in chronic migraine? A systematic review and meta-analysis [Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) 2020 recommendations] was made up to 19 April 2022. The results are encouraging: the combined treatment proved to afford ≥50% monthly headache days (MHDs)/frequency reduction respect to baseline in up to 58.8% of patients; in comparison, anti-CGRP mAbs reduce MHDs of 1.94 days from baseline and botulinum toxin of 1.86 days. Our study demonstrates for the first time that the combination therapy of onabotulinumtoxinA with anti-CGRP mAbs affords a reduction of 2.67 MHDs with respect to onabotulinumtoxinA alone, with moderate certainty of evidence. Adequately powered, good-quality studies are needed to confirm the response to combination therapy in terms of efficacy and safety. PROSPERO registration: CRD42022313640.